Accessing rural health services: Results from a qualitative narrative gerontological study. (28th June 2019) - Neville, Stephen; Napier, Sara; Adams, Jeffery; Shannon, Kay
Abstract: Objective: Explore how older adults' talk about accessing rural community health services. Methods: A qualitative narrative gerontological approach explored issues related to accessing health services in their community. Semi‐structured digitally recorded individual interviews were undertaken with 32 community‐dwelling older people aged between 75 and 93 years. A narrative data analytic process was undertaken. The COnsolidated criteria for REporting Qualitative research guidelines were followed to ensure rigour in this study. Results: Three collective narratives resulted from the data analytic process: (a) "accessing local health services"; (b) "accessing specialist services"; and (c) "accessing emergency services." Conclusions: Narrators identified a number of issues related to accessing rural health services. These included long waiting times, lack of continuity in care provision by doctors and difficulties accessing specialist and emergency services. Nurses were frequently cited as a reliable point of contact for these older people. Expansion of nursing roles would enhance the provision of rural health‐care services.